ANCAMAN INVASI IKAN ASING TERHADAP KEANEKARAGAMAN IKAN ASLI | Invasion Threats of Exotic Fish Species to Diversity of Indigenous Fish Species] - Sunarya Wargasasmita (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2005)
One of' several causal factors contributing to the declining of fish diversity is the introduction of exotic fish or alien species. However, the negative impacts of those exotic introduction still have little attention. We should take the lesson from experience of several country around the world, that the impacts of exotic species introduction are wide enough. These impacts not only causes of the freshwater environment degradation and the genetic deterioration of the host stock by hybridization, also causes the disruption of the native species and help the distribution of diseases and parasites, even causes the socioeconomic hardship for surrounding fishing communities (Welcome 1988). This paper presented comprehensive review of cases and impacts of exotic fish inlroiluelion.